Perioperative atrial fibrillation and risk of stroke after cardiac surgery: a systematic review and meta-analysis. (25th November 2020) - Wang, M.K; Chen, P; Meyre, P; Ali, M.Z; Heo, R; McIntyre, W; Healey, J; Whitlock, R; Lamy, A; Devereaux, P.J; Conen, D
Abstract: Background: Perioperative atrial fibrillation (POAF) after cardiac surgery has been associated with an increased risk of stroke. However, many previous studies have not systematically excluded patients with pre-existing AF. As such, the association between new-onset POAF and stroke risk has not been well established. Purpose: To perform a systematic review and meta-analysis on the short and long-term risks of stroke in patients experiencing new-onset POAF after cardiac surgery. Methods: We searched MEDLINE, EMBASE, and the Cochrane Library databases for studies comparing the risk of stroke in patients with versus without new-onset POAF after cardiac surgery. Studies were included in our review if they enrolled ≥100 patients and defined POAF as new-onset AF in patients with no history of preoperative AF. Data were independently extracted in duplicate. The quality of studies was assessed using the Newcastle Ottawa Scale. Random-effects meta-analysis was used to calculate summary risk ratios. Short-term stroke risk was calculated using events occurring either in-hospital or ≤30 days after surgery, and long-term risk was calculated using events occurring >30 days after surgery. Results: After reviewing 11, 791 citations, 46 studies met the inclusion criteria. These studies included 364, 822 patients, of which 76, 388 (20.9%) developed new-onset POAF. The incidence of stroke was higher among patients with POAF versus no POAF (n=44 studies; incidence 2.76% vs. 1.53%; relative risk (RR) 1.91, 95% CI 1.65–2.23; I2 = 78%). A sensitivity analysis of high-quality studies alone yielded similar results (n=9 studies; RR 1.74, 95% CI 1.31–2.30; I2 = 88%). Patients with POAF had a higher incidence of stroke both in the short-term (n=35 studies; 2.71% vs. 1.36%; RR 2.13, 95% CI 1.81–2.51; I2 = 69%) and long-term (n=20 studies; 1.6 vs. 1.0 per 100 patient-years; RR 1.39, 95% CI 1.24–1.57; I2 = 27%). The risk of stroke was increased in POAF patients across all types of cardiac surgery performed, including isolated CABG (n=19 studies; RR 1.93, 95% CI 1.60–2.32; I2 = 62%), isolated transcatheter aortic valve implantation (n=7 studies; RR 1.86, 95% CI 1.32–2.63; I2 = 0%), and studies including multiple procedure types (n=16 studies; RR 1.90, 95% CI 1.44–2.51; I2 = 89%). Conclusion: New-onset POAF after cardiac surgery is associated with an increased risk of stroke, both in the short and long term. The absolute risk difference is small, and randomized trials are needed to assess the efficacy and safety of treatment interventions in this patient population. Funding Acknowledgement: Type of funding source: None